Physicochemical properties and bioturbation analysis of high-temperature Daqu by functional microflora - Tingyan Xu; Anqin Zhu; Shuting Zhong; Yunsheng Wang; Chao Wang; Jin Zhang; Yincui Chen; Rui Wang; Chuanbo Zhang (Frontiers in Microbiology, 2025)
High-temperature Daqu (HTD) initiates the solid-state fermentation of sauce-aroma Baijiu by introducing essential microorganisms and enzymes, determining its unique flavor and quality. While biofortification with functional strains enhances HTD quality, the ecological dynamics and mechanisms of HTD fermentation influenced by synthetic functional microflora (SFM) remain unclear. Here, we prepared three different types of SFM inoculated into HTD, and studied their effects during spontaneous HTD fermentation. The results showed that all three SFM significantly increased the liquefaction power of the HTD, which the SG Daqu with the addition of yeast and Eurotium amstelodami synthetic flora were the most effective, and also had a significant increase in fermentation and esterification power. All three SFM increased the average relative abundance of Bacillus and decreased the relative abundance of Lactobacillus and Weissella, and enhanced the stability of the fungal community. The significant bioturbation effect of SFM on the bacterial community of HTD was predominantly observed during the 3-day fermentation period, while its substantial impact on the fungal community manifested during the 9-day fermentation. Meanwhile, the SFM influenced the community assembly pattern of HTD and stability of the network. Notably, PICRUSt2 revealed that the addition of SFM increased the potential ability of HTD to utilize energetic substances such as starch for metabolism and energy conversion, to generate ethanol and esters, and to facilitate ethanol metabolism. Overall, our work elucidated the regulatory mechanism of SFM on the longitudinal characteristics of microbial communities in the HTD fermentation stage, and provided a theoretical basis for further research on SFM to enhance the quality of HTD.